2020
DOI: 10.1111/jcmm.15558
|View full text |Cite
|
Sign up to set email alerts
|

Pan‐cancer analysis of alternative splicing regulator heterogeneous nuclear ribonucleoproteins (hnRNPs) family and their prognostic potential

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“… Xu et al (2020) observed that the expression of ALKBH5 and HNRNPC could predict the outcome of ESCA. In addition, HNRNPA2B1 is a binding protein and member of the hnRNP family ( Li et al, 2020 ). Recently, HNRNPA2B1 was recognized as a nuclear “reader” of m6A sites and was determined to affect alternative splicing patterns ( Alarcón et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“… Xu et al (2020) observed that the expression of ALKBH5 and HNRNPC could predict the outcome of ESCA. In addition, HNRNPA2B1 is a binding protein and member of the hnRNP family ( Li et al, 2020 ). Recently, HNRNPA2B1 was recognized as a nuclear “reader” of m6A sites and was determined to affect alternative splicing patterns ( Alarcón et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The genes HNRNPA1, HNRNPA2B1 and HNRNPC are ubiquitously expressed heterogeneous nuclear ribonucleoproteins (hnRNPs) involved in mRNA metabolism, splicing and regulation of alternative splicing events. Indeed, these genes are associated with carcinogenesis and metastasis with a diverse set of tumor types (66,67). The spliceosomal host machinery is especially important for the high-risk HPV life cycle and transformation in CC.…”
Section: Discussionmentioning
confidence: 99%
“…Selective splicing produces cellular proteins that are selectively expressed in a tissue-specific and time-dependent manner and participate in a variety of regulatory pathways including Abnormal splicing may lead to the production of abnormal mRNA isomers that encode mutant proteins, which have increased or decreased function and participate in cell transformation and the development and metastasis of cancer (21). The functions of spliceosome complexes and splicing modulators have been widely studied in cancer (22). In particular, splicing regulators such as snRNPs, hnRNPs, and SR proteins have been proven to play the role of carcinogenic or tumor suppressor proteins in diverse types of cancer (23,24), including breast (25) and lung cancer (26).…”
Section: Discussionmentioning
confidence: 99%